THE EFFECT OF PAD, BALANCED FUNDS, AND REGIONAL EXPENDITURES ON FINANCIAL PERFORMANCE OF REGIONAL GOVERNMENTS IN DISTRICT/CITY NORTH SUMATRA PROVINCE 2017-2020 - Utari, Ulfa; Maksum, Azhar; Situmeang, Chandra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this study was to determine and analyze the effect of Regional Original Income (PAD), Balancing Funds, and Regional Expenditures on the Financial Performance of Regency / City Governments in North Sumatra Province. The population of this research is districts/cities in North Sumatra Province as many as 33 districts/cities in the 2017-2020 observation year. The type of sample in this study used a saturated sample where the entire population was sampled. The data was processed using panel data regression statistical tests with the help of SPSS software.The results of this study prove that Regional Original Income, Balancing Funds, and Regional Expenditures have a simultaneous effect on the Financial Performance of Regency / City Governments in North Sumatra Province. Partially Local Original Income, Balancing Funds, and Regional Expenditures have a significant positive effect on the Financial Performance of Regency/City Governments in North Sumatra Province